Evaluation of perfusate solution after ex vivo lung perfusion - Dobrovolná, Terezie (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2023)
The aim of this master’s thesis is to introduce lung perfusion procedures and determine the parameters that are connected to the state of the lungs after perfusion and during preservation. In the perfusion process and for storing the lung, the phosphate-buffered saline (PBS) solution is used. The work focuses mainly on the parameters that can be measured and evaluated in the perfusate solution during the perfusion and preservation of the lungs such as pH, total dissolved solids, and proteins. These factors can be measured according to several procedures that are based on different principles. The mentioned process has been selected and implemented with regard to availability, feasibility, and appropriateness given. The pH and TDS parameters have been acquired by electrodes. Therefore, sensor calibration is an integral part of the measure ment. The concentration of the proteins was measured with the Bradford assay where it is important to follow the established protocol. Materials for that were present and provided in the Tissue engineering laboratory. Another intention is to assess the state of the lung tissue, meaning how the lungs gradually change their appearance, weight, and mechanical properties over time. The weight is obtained with the calibrated load cell sensor. For this sensor, a platform had to be assembled in order to function correctly and with great accuracy. From the field of mechanical properties of the lungs, the compliance and PV loops have been selected and presented. Five lungs were used for measurement. The appearance of the lungs changed over time and the necrosis was progressing. The lung viability was preserved with the PBS solution with balanced pH. The value of pH was maintained around pH 7. The concentration of the total dis solved solids (TDS) was determined and similar values were obtained in all lungs because the same solution was used. The TDS fluctuated slowly same as pH because they are correlated. The weight of the lungs decreased with passage of the time as expected. Protein concentration increased over time. That can indicate the inflammatory processes in the lung tissue or lung injury. The surface temperature was also obtained with a laser thermometer and decreasing values were noted with increasing storage time. Static compliance had unexpected charac teristics in some of the lungs. This was probably influenced by leakage due to an unsecured trachea. The last parameter was PV loops. The shape of the PV loops looked good until 48h in the majority of the loops. Then, the shape flatted and the shortage of curves appeared due to shortness of breath.

The aim of this master’s thesis is to introduce lung perfusion procedures and determine the parameters that are connected to the state of the lungs after perfusion and during preservation. In the perfusion process and for storing the lung, the phosphate-buffered saline (PBS) solution is used. The work focuses mainly on the parameters that can be measured and evaluated in the perfusate solution during the perfusion and preservation of the lungs such as pH, total dissolved solids, and proteins. These factors can be measured according to several procedures that are based on different principles. The mentioned process has been selected and implemented with regard to availability, feasibility, and appropriateness given. The pH and TDS parameters have been acquired by electrodes. Therefore, sensor calibration is an integral part of the measure ment. The concentration of the proteins was measured with the Bradford assay where it is important to follow the established protocol. Materials for that were present and provided in the Tissue engineering laboratory. Another intention is to assess the state of the lung tissue, meaning how the lungs gradually change their appearance, weight, and mechanical properties over time. The weight is obtained with the calibrated load cell sensor. For this sensor, a platform had to be assembled in order to function correctly and with great accuracy. From the field of mechanical properties of the lungs, the compliance and PV loops have been selected and presented. Five lungs were used for measurement. The appearance of the lungs changed over time and the necrosis was progressing. The lung viability was preserved with the PBS solution with balanced pH. The value of pH was maintained around pH 7. The concentration of the total dis solved solids (TDS) was determined and similar values were obtained in all lungs because the same solution was used. The TDS fluctuated slowly same as pH because they are correlated. The weight of the lungs decreased with passage of the time as expected. Protein concentration increased over time. That can indicate the inflammatory processes in the lung tissue or lung injury. The surface temperature was also obtained with a laser thermometer and decreasing values were noted with increasing storage time. Static compliance had unexpected charac teristics in some of the lungs. This was probably influenced by leakage due to an unsecured trachea. The last parameter was PV loops. The shape of the PV loops looked good until 48h in the majority of the loops. Then, the shape flatted and the shortage of curves appeared due to shortness of breath.
Evaluation of perfusate solution after ex vivo lung perfusion
Keywords: Lung perfusion; Preservation; Lung function; Status of the lung; Porcine lungs; Measurements in solution; Biomarkers; Lung perfusion; Preservation; Lung function; Status of the lung; Porcine lungs; Measurements in solution; Biomarkers